KARAKTERISTIK FISIK, MEKANIK, DAN THERMAL BIOKOMPOSIT PVA DIPERKUAT NANOSELULOSA SERAT WARU - SERBUK CaCO3 - Suteja; Syarif Hidayatullah (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Polyvinyl alcohol (PVA) biocomposites are a potential material to replace conventional plastics, but mechanical strength and thermal resistance are still low. To overcome these limitations, reinforcement from waru fiber nanocellulose (NCW) and calcium carbonate (CaCO₃) fillers are added to PVA bioplastics. Biocomposites formulator were mixed using a magnetic stirrer until gel formed, then poured onto glass and dried in oven for 12 hours at 60 °C. The density results showed an increase to 2.15 g/cm3 and a thickness of 1.32 mm after adding CaCO3. Meanwhile, PVA-NCW had a density and thickness of 1.27 g/cm3 and 0.26 mm respectively. This indicates as a major factor in increasing the tensile strength of biocomposites. The fillers play a role in increasing the tensile strength of biocomposites through better surface bonding. In addition, the interfacial bonding between PVA and the fillers has been confirmed by FTIR results. SEM observation shows the presence of clumps of NCW and CaCO3. In line with the tensile testing, the highest thermal resistance was also found in the PVA-CaCO3 sample. This is in line with the amount of residue produced by the PVA-CaCO3 sample 6.38%. The developed biocomposite offers great potential as a conventional plastics substitute.